What Makes Foreign Knowledge Attractive to Domestic Innovation Managers? - Wolfgang Sofka (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2007)
This study focuses on the early stages of international innovation activities, i.e. the organizational processes through which promising ideas from around the globe are collected and evaluated. We ask: What characteristics make foreign knowledge interesting to domestic R&D managers? We envision this process as a balancing act between direct transaction costs for communication and coordination and indirect transaction costs from overlooking or misinterpreting important global trends. These hypotheses are tested through a conjoint analysis among 158 heads of R&D departments of German high-tech firms. We find that uncertainty avoidance is the most important driver. Radically new ideas from dynamic markets are most attractive and must not be overlooked. Complementarities with existing knowledge stocks and low language barriers are also important but to a lesser degree. Interestingly, we find no distinction between market and technological impulses.
Keywords: O32; O31; F23; 330; Globalization; sensing; innovation impulses; conjoint analysis; Industrielle Forschung; Wissenstransfer; Innovationsmanagement; Entscheidung bei Unsicherheit; Globalisierung; Deutschland